Blue Morpho Butterfly Morpho peleides Kollar (Lepidoptera: Nymphalidae) - Haleigh A. Ray; Jacqueline Y. Miller (EDIS)
The blue morpho butterfly, also known as the peleides blue morpho or common blue morpho, is a brightly colored butterfly abundant in tropical environments in Central and South America. It can be seen flying in open areas such as paths, trails, forest edges, and rivers. In the United States, it is often featured in museums and zoos that have butterfly houses or butterfly rainforests. This five-page fact sheet about the popular butterfly was written by Haleigh A. Ray and Jacqueline Y. Miller, and published by the UF Department of Entomology and Nematology, August 2015. (Photo credit: Andrei Sourakov, McGuire Center or Lepidoptera and Biodiversity, Florida Museum of Natural History, University of Florida)